Netrin-1 Promotes Synaptic Formation and Axonal Regeneration via JNK1/c-Jun Pathway after the Middle Cerebral Artery Occlusion - Zheng, Mouwei; Chen, Ronghua; Chen, Hongbin; Zhang, Yixian; Chen, Jianhao; Lin, Peiqiang; Lan, Quan; Yuan, Qilin; Lai, Yongxing; Jiang, Xinhong; Pan, Xiaodong; Liu, Nan (Frontiers in Cellular Neuroscience, 2018)
As a secreted axon guidance molecule, Netrin-1 has been documented to be a neuroprotective factor, which can reduce infarct volume, promote angiogenesis and anti-apoptosis after stroke in rodents. However, its role in axonal regeneration and synaptic formation after cerebral ischemic injury, and the related underlying mechanisms remain blurred. In this study, we used Adeno-associated vectors carrying Netrin-1 gene (AAV-NT-1) to up-regulate the expression level of Netrin-1 in rats’ brain after middle cerebral artery occlusion (MCAO). We found that the up-regulated level of Netrin-1 and its receptor DCC promoted axonal regeneration and synaptic formation; the overexpression of Netrin-1 activated the JNK1 signaling pathway; these effects were partially reduced when JNK1 signaling pathway was inhibited by SP600125 (JNK specific inhibitor). Taken together, these findings suggest that Netrin-1 can facilitate the synaptic formation and axonal regeneration via the JNK1 signaling pathway after cerebral ischemia, thus promoting the recovery of neural functions.